2016
DOI: 10.1515/mgr-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

The effects of river patterns on riparian vegetation: A comparison of anabranching and single-thread incised channels

Abstract: Riparian vegetation reflects the current conditions and the dynamics of streams. The floodplain vegetation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…On one hand, this suggests that distance from the river may either have no significant impact on the distribution of species inhabiting the riparian zone, or that they have a significant influence on species composition alone [42]. On the other hand, there might be other environmental gradients [9,11,43] or anthropogenic disturbances [14,17,18] that control the characteristics of species evenness or diversity in this ecosystem that were not included in the present study.…”
Section: Variation In Plant Species Diversity Along Lateralmentioning
confidence: 89%
“…On one hand, this suggests that distance from the river may either have no significant impact on the distribution of species inhabiting the riparian zone, or that they have a significant influence on species composition alone [42]. On the other hand, there might be other environmental gradients [9,11,43] or anthropogenic disturbances [14,17,18] that control the characteristics of species evenness or diversity in this ecosystem that were not included in the present study.…”
Section: Variation In Plant Species Diversity Along Lateralmentioning
confidence: 89%
“…The results showed that different plant habitat conditions occur in the incised channel reach and in the multi-thread channel reach [12]. The analysis of the Shannon-Wiener and Simpson's indices demonstrated a larger variety of habitat conditions in the floodplain area along the multi-thread river channel (see fig.…”
Section: Channel Transformations and Their Effect On Riverine Ecosystmentioning
confidence: 89%
“…Similarly, the analysis of groundwater detected hydrological conditions changes of the floodplain which is gradually drying out in the Morávka River basin (see fig. 2A) [12].…”
Section: Channel Transformations and Their Effect On Riverine Ecosystmentioning
confidence: 99%
See 2 more Smart Citations